2021
DOI: 10.3390/app11083583
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Clinical Characteristics of Korean Temporomandibular Disorder Patients

Abstract: The aims of this study were to investigate the gender differences in signs and symptoms of Korean Temporomandibular Disorder (TMD) patients based on Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) and psychosocial characteristics. A total of 1052 patients with TMD were evaluated with a questionnaire for medical history, clinical symptoms, and contributing factors, clinical examination based on RDC/TMD, and radiographic examination. RDC/TMD axis II and Symptom Checklist-90-Revision (SCL-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…It was also mentioned that there was a decreasing distribution of the disease with age, which could indicate the limiting feature of the disease. The present study highlighted the presence of a higher female predilection, which is similar to the studies reported by Bagis et al, Ferreira et al, and Jo et al 13 14 15 Furthermore, the average age of the population is 41 ± 16 years, with the minimum age being 19 and the maximum being 68, similar to a study by Ferreira et al 14…”
Section: Discussionsupporting
confidence: 92%
“…It was also mentioned that there was a decreasing distribution of the disease with age, which could indicate the limiting feature of the disease. The present study highlighted the presence of a higher female predilection, which is similar to the studies reported by Bagis et al, Ferreira et al, and Jo et al 13 14 15 Furthermore, the average age of the population is 41 ± 16 years, with the minimum age being 19 and the maximum being 68, similar to a study by Ferreira et al 14…”
Section: Discussionsupporting
confidence: 92%
“…It primarily affects teens and 20s, and the prevalence rises with age, with women being more affected than men [1,2]. A recent domestic study also found a rapid increase in the number of patients in their 20s, but the cause is unknown [2]. Therefore, in this study, while there are numerous causes of TMDs, salivary cortisol was measured for the group in their 20s to assess the relationship with stress (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…TMDs cause temporomandibular joint and masticatory muscle pain and dysfunction. It primarily affects teens and 20s, and the prevalence rises with age, with women being more affected than men [1,2]. A recent domestic study also found a rapid increase in the number of patients in their 20s, but the cause is unknown [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a meta-analysis before the pandemic by Bueno et al [ 53 ] reported a higher prevalence and greater tendency for females to have TMD than males. In 2021, another study [ 54 ] carried out in South Korea revealed more TMD symptoms in females, who presented a higher prevalence of pain and muscle palpitations compared to males.…”
Section: Discussionmentioning
confidence: 99%